Case Study: Implementation of Use of Warm Compress Therapy to Reduce Pain Intensity in DHF Patients - Asep Gunawan; Nida Siti Padilah; Mutia Dwi Mulyani; Jajuk Kusumawaty; Adi Nurapandi (Genius Journal, 2023)
Objective: To present warm compress intervention nursing care as an effort to overcome pain to children who experience DHF with heartburn problems directly in the Melati Room BLUD Banjar City General Hospital. Methods: The design of this research is descriptive with a case study approach using nursing care that refers to the IDHS and SIKI books. The subject of this case study is only one person, namely a child who has DHF with heartburn problems in the Melati Room BLUD RSU Banjar City, with data collection techniques including interviews, observation, physical examination and documentation studies. Results: The results of the case study at the assessment stage showed that the client complained of heartburn. With the intervention and implementation used is a warm compress. During the intervention process until the evaluation took place, it went as expected without any obstacles. There is a change in the pain scale from the original 5 scale to a 0 scale. Conclusion: The conclusion of nursing care for children with dengue hemorrhagic fever (DHF) with heartburn problems is well resolved. Giving a warm compress intervention is effective in reducing pain intensity, the pain scale which was originally a scale of 5 has disappeared (scale 0).